Validation of Rapid Antibody (IgM – IgG) Test Kit for SARS-CoV-2 Infection in Surabaya, Indonesia - Museyaroh Museyaroh; Puspa Wardani; Aryati Aryati; Evy Diah Woelansari (Universitas Nahdlatul Ulama Surabaya, 2022)
At the beginning of the Corona Virus Disease 2019 (COVID-19) pandemic, rapid test examinations were widely used as a screening for Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection. The purpose of this examination was to detect SARS-CoV-2 IgM/IgG antibodies in the patient's body. One of these tests uses the immunochromatographic method. This study aims to determine the validity of immunochromatography. The study was conducted from August to September 2020. The sample used in this study was 100 patients. The research was conducted at Husada Utama Hospital Surabaya, Indonesia. According to the study's findings, the Zybio brand reagent kit has an accuracy of 85%, a sensitivity of 82%, a specificity of 88%, a positive predictive value of 87%, and a negative predictive value of 83%. In the group of patients who experienced clinical symptoms, < 7 had a sensitivity of 50%, specificity of 88%, positive predictive value of 60%, negative predictive value of 83%, and accuracy of 77.94% while the group of patients experiencing clinical symptoms > 7 days, had a sensitivity value of 100 %, specificity of 88%, positive predictive value of 84%, negative predictive value of 100%, and accuracy of 92.68%. Based on these results, the conclusion is that the Zybio brand reagent kit has a relatively high sensitivity, specificity, positive predictive value, negative value, and sample accuracy. In the group with clinical sensitivity < 7 days, the positive predictive value and accuracy are lower than the sample group with clinical symptoms > 7 days but have the same specificity.